Evaluating relapse prophylaxis in addition to interdisciplinary multimodal pain therapy for back pain: a randomised controlled trial - Schmetsdorf, Julia; Krüger, Kathrin; Posselt, Jacqueline; Werner, Runde; Zechel, Hans-Georg; Kohlmann, Thomas; Krauth, Christian (Journal of rehabilitation medicine, 2025)
Objective: This study aimed to evaluate the effectiveness of a 12-month relapse prophylaxis following a 4-week interdisciplinary multimodal pain therapy approach for patients with back pain. The study examined whether the intervention reduced days of incapacity to work (primary outcome) and improved functional capacity and health-related quality of life (secondary outcomes) compared with interdisciplinary multimodal pain therapy alone. Design: A randomized controlled trial was conducted. The recruitment period was 24 months. Subjects/Patients: The study comprised 297 employed patients from a rural region in north-west Germany, diagnosed with back pain in different regions of the spine. Methods: The analyses were based on quantitative data: claims data and questionnaire data. Results: The results showed a mean of 70.07 days of incapacity to work after the interdisciplinary multimodal pain therapy for the control group and a lower mean of 56.41 days for the intervention group. The group difference was not significant (p = 0.259). Analysis of change scores revealed statistically significant larger improvements of functional capacity and health-related quality of life in the intervention group. Conclusion: Findings of this study show improvements in the secondary outcomes. The results indicate that further studies are needed to determine how to sustainably reduce days off work due to back pain.